Effectiveness of Magnetic Stimulation in the Treatment of Urinary Incontinence: A Systematic Review and Results of Our Study - David Lukanović (MDPI AG, 2021)
Urinary incontinence (UI) is becoming an increasingly common health problem. UI treatment can be conservative or surgical. This paper focuses on the effectiveness of magnetic stimulation (MS) in the treatment of UI. We performed a systematic review in order to combine and compare results with results from our clinical study. A clinical prospective non-randomized study was carried out at the Ljubljana University Medical Center’s Gynecology Division. It included 82 randomly selected female patients, irrespective of their UI type. The success rate of using MS in treating UI was based on standardized ICIQ-UI SF questionnaires. Patients completed 10 therapy sessions on MS, and follow-up was performed 3 months after the last therapy session. UI improved after treatment with MS. The ICIQ-UI SF score improved in patients regardless of the type of UI. However, the greatest decrease in post-treatment assessment ICIQ-UI SF scores was seen in patients with stress urinary incontinence (SUI). Based on the findings described above, it can be concluded that MS is a successful non-invasive conservative method for treating UI. Future studies are necessary, all of which should include a large sample size, a control group, an optimal research protocol, pre-treatment analyses, standardization, and longer follow-ups.